India’s Nuclear Security Vulnerabilities and Commitments : Considering Cyber Threats and Nuclear Material Trafficking - Zahoor Ahmad Mir; Adil Bashir Parry (PT FORMOSA CENDEKIA GLOBAL, 2022)
Nuclear security refers to the prevention and detection of illegal or purposeful unauthorised acts with nuclear material, other radioactive material, associated facilities, or associated activities, as well as the reaction to such criminal or intentional acts. The nuclear domain is constantly confronted with the problems posed by existing and developing dangers related to nuclear security. After the September 11 terrorist attacks in the United States, public perceptions of nuclear security concerns grew significantly. The advancement of technology has increased the number of security breaches. This is evidenced by the increasing number of cyberattacks on nuclear power plants. After this point in time, the global nuclear community has channelled its efforts toward the establishment and strengthening of global institutions and norms, as well as international regimes, in order to establish and/or maintain robust and protective mechanisms in the domain of nuclear security. Ultimately, the individual sovereign nation has the burden of responsibility for nuclear security, with India being one such responsible nuclear actor. There are a variety of reasons why nuclear security is crucial for India. Due to its extensive nuclear programme and the dispersion of its atomic energy installations around the country, India has a huge vulnerability. Additionally, given India’s unfriendly immediate neighbours, the country is particularly vulnerable to nuclear terrorism, cyberattacks, and other new threats. The study examines India’s nuclear security initiatives, the dangers they confront, and the possible means to counter the threats.